A high-permeability polyimide helium separation membrane, a preparation method and applications thereof

CN122499654BActive Publication Date: 2026-10-09TIANJIN POLYTECHNIC UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610993864.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09
Estimated Expiration
2046-07-06

AI Technical Summary

Technical Problem

然而,此类技术往往过于偏重材料骨架的分子设计,忽略了这些PI在干-湿法中空纤维纺丝过程中极其复杂的流变学不稳定性

Benefits of technology

1. 本发明通过选用重均分子量(10万-40万)的含氟聚酰亚胺树脂,含氟聚酰亚胺树脂中具有强电负性、大空间位阻的三氟甲基(-CF3)基团,显著增加了膜材料的自由体积分数(FFV),为氦气分子提供了极低阻力的快速扩散通道,同时提高了氦气/甲烷溶解选择性。在25℃、0.2 MPa测试条件下,制备得到的含氟聚酰亚胺的He渗透通量最高可达1000GPU,对He/CH4的选择性最高可达120。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122499654B_ABST
    Figure CN122499654B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of gas separation, and discloses a high-permeability polyimide helium separation membrane, a preparation method and application. A casting solution system with low solid content (15-30 wt%) is constructed by using fluorine-containing polyimide resin with a weight average molecular weight of 100-400 thousand, the fluorine-containing polyimide resin is prepared through polycondensation reaction of a dianhydride monomer and a diamine monomer, the diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole or 2-(4-aminophenyl)-5-aminobenzoxazole, and the dianhydride monomer is 4,4'-(hexafluoroisopropylene) diphthalic anhydride; a gradient asymmetric hollow fiber membrane with a defect-free skin layer structure is successfully constructed by using a dry-wet spinning process with high shearing and high yarn speed. The obtained separation membrane has super-high helium flux, high selectivity and compression strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gas separation technology, and specifically to a high-permeability polyimide helium separation membrane, its preparation method, and its applications. Background Technology

[0002] Helium (He) is a scarce, non-renewable resource. Due to its unique physicochemical properties, including an extremely low boiling point, very small molecular diameter, high thermal conductivity, and chemical inertness, it is widely used in cutting-edge technology fields such as aerospace, CT, semiconductor manufacturing, nuclear magnetic resonance (MRI), low-temperature superconductivity research, fiber optic production, and nuclear fusion. The demand for helium is increasing year by year; however, helium resources are mainly concentrated in associated gas from natural gas.

[0003] Currently, traditional methods for extracting helium from natural gas mainly include cryogenic separation and pressure swing adsorption (PSA). Cryogenic separation utilizes the differences in boiling points of components in a gas mixture, purifying helium through multiple condensations and distillations. Although this technology is relatively mature and has a large processing capacity, it requires huge equipment investment, consumes extremely high amounts of energy, and has an extremely complex process, making it economical only for natural gas with a high helium content. Pressure swing adsorption mainly utilizes the differences in the adsorption capacity of adsorbents for different gas components, but when processing large-scale gases or systems with extremely low helium content (e.g., less than 500 ppm), it suffers from inherent drawbacks such as large adsorption tower volume, long cycle time, and difficulty in achieving continuous operation.

[0004] Membrane separation technology, as a green and low-energy-consumption separation method, has shown great application potential in the fields of natural gas helium extraction and helium recovery. Although there is a difference in the kinetic diameter between helium and methane (He is 2.6 Å, CH4 is 3.8 Å), achieving ultra-high throughput while ensuring high selectivity places extremely high demands on the micropore size of the membrane material and the dry-wet spinning process. Polyimide (PI) has become the preferred material for high-performance gas separation due to its excellent physicochemical stability. However, existing work on He / CH4 separation generally suffers from the bottleneck of "difficulty in balancing throughput and selectivity".

[0005] The commonly used modification strategies and their drawbacks in existing technologies are as follows: (1) Introducing cross-linking structures to improve the density of membrane materials. For example, Chinese patent CN105289337A discloses a cross-linkable polyimide gas separation membrane, which uses conventional aromatic polyimide resin, or densification heat treatment such as physical blending and chemical cross-linking to suppress the permeation of large molecular methane. Although this approach can achieve better sieving selectivity, it will lead to a sharp decrease in the intrinsic free volume inside the membrane matrix, and its helium permeation flux is generally between 10-50 GPU. This will result in a huge required membrane area and excessively high investment costs for the components and equipment.

[0006] (2) Introducing fluorine-containing structures or thermal rearrangement structures to increase the interchain spacing of materials: For example, Chinese patent CN113631248A attempts to forcibly expand the interchain spacing by introducing fluorine-containing macromolecular functional groups with large steric hindrance (such as 6FDA-6FpDA type); Chinese patent CN113996193A uses 6FDA anhydride and o-hydroxy diamine monomer condensation, and then uses in-situ thermal rearrangement technology to convert o-hydroxyl groups into rigid benzoxazole rings, thereby significantly increasing the porosity and rigidity of the membrane, intending to improve the permeability of He. However, such technologies often focus too much on the molecular design of the material skeleton and ignore the extremely complex rheological instabilities of these PIs during dry-wet hollow fiber spinning. Due to the lack of fine film-forming kinetic control, transient phase separation or local gelation is very likely to occur during spinning, making it impossible to make the effective transport resistance layer thin in the process, and its helium permeation flux is often difficult to stably exceed 200 GPU.

[0007] In summary, the key technical challenge that urgently needs to be addressed in the development of high-performance helium extraction membrane equipment is how to overcome the limitations of existing technologies in terms of flux by leveraging the properties of the resin and deeply synergistically controlling the film-forming process (such as low-temperature spinning, high supply, and high drawing) while ensuring high screening accuracy, and achieving a revolutionary leap in helium permeation flux to the 300-1000 GPU level, while maintaining the structural integrity and long-term pressure resistance of hollow fiber membranes under industrial high-pressure natural gas conditions. Summary of the Invention

[0008] To address the technical shortcomings of existing helium separation membrane materials, such as difficulty in balancing helium permeation flux and selectivity, and numerous defects in the dense skin layer, this invention provides a high-permeability polyimide helium separation membrane, its preparation method, and its application. By utilizing high-molecular-weight polyimide resin and designing a low-solids-content casting solution formulation, a gradient asymmetric hollow fiber membrane with ultra-high helium permeability, high selectivity, and compressive strength is directly constructed through a combination of high supply and high shear rheological conditions.

[0009] The present invention adopts the following technical solution: This invention discloses a method for preparing a high-permeability polyimide helium gas separation membrane, comprising the following steps: S1. Dissolve the fluorinated polyimide resin in a mixed solvent, stir until homogeneous, and after degassing treatment, obtain a casting solution with a solid content of 15 wt%-30 wt%. The fluorinated polyimide resin is prepared by polycondensation reaction of dianhydride monomer and diamine monomer. The diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) or 2-(4-aminophenyl)-5-aminobenzoxazole (APBOA), and the dianhydride monomer is 4,4'-(hexafluoroisopropene)phthalic anhydride (6FDA).

[0010] S2. The casting solution and core solution obtained in step S1 are used for dry-wet hollow fiber spinning through a spinneret. The nascent membrane fibers extruded from the spinneret pass through an air gap and a coagulation bath in sequence. Then, the membrane fibers are axially stretched and wound using a take-up roller to obtain a nascent membrane fiber bundle.

[0011] S3. The nascent membrane fiber bundles obtained in step S2 are sequentially immersed in deionized water, anhydrous ethanol and n-hexane for solvent exchange, and then dried to obtain the high-permeability polyimide helium separation membrane.

[0012] Preferably, the fluorinated polyimide resin has a weight-average molecular weight of 100,000 to 400,000 and a dispersion of less than 2.5.

[0013] Preferably, the preparation method of the fluorinated polyimide resin is as follows: using N-methylpyrrolidone as a solvent, diamine and dianhydride in an equimolar ratio are reacted at a gradient temperature of 180-190 °C for 18-24 h under an argon atmosphere to obtain the fluorinated polyimide resin.

[0014] Preferably, the mixed solvent comprises a good solvent and a poor solvent in a mass ratio of 60:40 to 90:10. The good solvent includes one or more of NMP (N-methylpyrrolidone), DMAc (N,N-dimethylacetamide), and DMF (N,N-dimethylformamide); the poor solvent includes one or more of ethanol, propanol, methanol, and isopropanol. Preferably, the dissolution process in step S1 specifically involves continuously stirring at 60-80°C for 12-24 hours until the fluorinated polyimide resin is completely dissolved.

[0015] Preferably, the degassing process in step S1 is vacuum degassing or atmospheric pressure degassing, with a degassing time of 3-36 hours and a vacuum degree of 0-90 kPa.

[0016] Preferably, in step S2, the spinning temperature is 25°C, the length of the air gap is 0.1-200 mm, the flow rate of the casting solution and the core solution is 0.6-6.0 mL / min, and the coagulation bath is a deionized water coagulation bath at 0-40°C.

[0017] Preferably, in step S2, the core fluid is a mixed solution of N-methylpyrrolidone and water with a mass ratio of 90:10 to 80:20, more preferably 80:20.

[0018] Preferably, in step S2, the take-up speed of the take-up roller is 15-35 m / min.

[0019] Preferably, in step S3, the solvent exchange process is as follows: soaking in deionized water for 1-48 hours at a water temperature between 10-40 °C, soaking in ethanol for 0.1-48 hours, and soaking in n-hexane for 0.1-48 hours; after the solvent exchange is completed, the content of high-boiling-point solvent in the membrane fiber is below 1000 ppm; the drying temperature is 25 °C, and the drying time is 24 hours.

[0020] The second aspect of this invention discloses a high-permeability polyimide helium separation membrane obtained by the above preparation method. The separation membrane is an asymmetric hollow fiber membrane with a dense skin layer and a porous support layer. Under test conditions of 25°C and 0.2 MPa, its helium permeation flux is 600-1000 GPU, the helium / methane selectivity is 80-120, and the burst pressure is above 5.0 MPa.

[0021] The third aspect of this invention discloses the application of the above-mentioned high-permeability polyimide helium separation membrane in the fields of natural gas helium extraction, helium recovery or helium purification.

[0022] Advantages and beneficial effects of the present invention: 1. This invention utilizes fluorinated polyimide resins with a weight-average molecular weight (100,000-400,000). The trifluoromethyl (-CF3) groups in these resins, exhibiting strong electronegativity and significant steric hindrance, significantly increase the free volume fraction (FFV) of the membrane material, providing a fast diffusion channel with extremely low resistance for helium molecules and simultaneously improving the helium / methane solubility selectivity. Under test conditions of 25°C and 0.2 MPa, the prepared fluorinated polyimide exhibits a maximum He permeation flux of 1000 GPU and a maximum He / CH4 selectivity of 120.

[0023] 2. In the dry-wet hollow fiber spinning process, the present invention provides a high supply of liquid (flow rate of 0.6-6.0 mL / min) through a precision gear pump, controls the take-up speed, and simultaneously utilizes the synergistic effect of the high shear force generated by the narrow slit of the composite spinneret and the high axial tensile stress in the air gap region to cause some polymer chains to align.

[0024] 3. This invention controls the solid content of the casting liquid within a low range of 15 wt%-30 wt%, which significantly reduces the mass transfer resistance of the skin layer, a prerequisite for achieving intrinsically high throughput. Simultaneously, by controlling the weight-average molecular weight of the polyimide resin within a high molecular weight range of 100,000-400,000, and utilizing the chain entanglement effect of high molecular weight polyimide, defect-free hollow fiber membrane materials can still be formed even at low solid content, thereby achieving high throughput and high selectivity.

[0025] In summary, this invention successfully prepared a gradient asymmetric hollow fiber membrane with a defect-free skin by selecting high molecular weight (100,000-400,000) fluorinated polyimide, designing a low solids content (15-30 wt%) casting solution, and introducing a high take-up speed (15-35 m / min) and low temperature (25℃) spinning process during the dry-wet spinning process. This membrane maintains high selectivity while increasing helium permeation flux, and also possesses excellent mechanical strength and compressive stability, making it suitable for demanding applications such as natural gas helium extraction and helium recovery. Attached Figure Description

[0026] Figure 1 This is a spinning process diagram of Embodiment 1 of the present invention; Figure 2 The GPC curve of the 6FDA-APBIA resin in Example 1 of this invention; Figure 3 A macroscopic photograph of the casting solution prepared with 6FDA-APBIA resin in Example 1 of this invention; Figure 4 This is a photograph of the high-permeability polyimide helium separation membrane of Example 1 of the present invention; Figure 5 This is a SEM image of a single membrane filament of the high-permeability polyimide helium separation membrane of Example 1 of the present invention; Figure 6 This is a comparison chart of the separation performance of the separation membranes in Examples 1-4 of the present invention and the prior art; Figure 7 The stress-strain curves are for the separation membranes of Examples 1-4 of the present invention. Detailed Implementation

[0027] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the implementation of the present invention is not limited thereto.

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the experimental materials used are all available from conventional commercial sources unless otherwise specified. All percentages mentioned in the following examples are mass percentages (wt%) unless otherwise specified.

[0029] Example 1 A method for preparing a high-permeability polyimide helium gas separation membrane includes the following steps: S1. Preparation of casting solution: Under an argon atmosphere, equimolar amounts of 6FDA and APBIA were dissolved in NMP, and then the mixture was subjected to a condensation reaction at a gradient temperature of 180-190℃ for 5 h to obtain a 6FDA-APBIA resin with a weight-average molecular weight of 250,000 (GPC curve shown). Figure 2 ); 6FDA-APBIA resin was vacuum dried at 120°C for 2 hours to remove adsorbed water. The dried 6FDA-APBIA resin was dissolved in a mixed solvent of NMP and anhydrous ethanol at a mass ratio of 75:25, with stirring at 200 rpm to control the solid content of 6FDA-APBIA resin in the casting solution to 18 wt%. The solution was continuously mechanically stirred at 60°C for 24 hours until completely dissolved. Subsequently, it was pressure filtered at 50°C and degassed under vacuum for 12 hours at a vacuum degree of -95 kPa to obtain a homogeneous and transparent casting solution. A macroscopic photograph of the casting solution is shown below. Figure 3 As shown.

[0030] S2, Dry-Wet Hollow Fiber Spinning: Spinning flow chart as shown below Figure 1 As shown, the spinning device is started, and the feed tank, conveying pipeline and composite spinneret are all preheated to a constant 25°C. The casting solution is delivered to the outer annulus of the spinneret through a precision gear pump, and the flow rate of the casting solution is controlled at 4.5 mL / min. Simultaneously, the core solution is injected into the central tube. The core solution is a mixture of N-methylpyrrolidone and water with a mass ratio of 80:20, and the flow rate of the core solution is 4.5 mL / min. The nascent membrane filaments extruded from the spinneret pass through a 100 mm air gap and then enter a 25°C deionized water coagulation bath to solidify and form the membrane filaments. The membrane filaments are axially stretched and wound using a take-up roller at a take-up speed of 25 m / min to obtain the nascent membrane filament bundle.

[0031] S3. Washing, Solvent Exchange, and Direct Drying: The wound nascent membrane fiber bundle was immersed in flowing deionized water at 25 °C for 48 hours to remove residual solvent. Subsequently, the nascent membrane fiber bundle was sequentially immersed in anhydrous ethanol for 24 hours and then in n-hexane for 24 hours to perform a cascade solvent exchange with decreasing surface tension. Afterward, the nascent membrane fiber bundle was removed and directly dried at room temperature (25 °C) for 24 hours without subsequent high-temperature heat treatment or surface defect repair coating, thus obtaining the final high-permeability polyimide helium separation membrane.

[0032] A physical image of the high-permeability polyimide helium gas separation membrane is shown below. Figure 4 As shown, an electron microscope scan of a single membrane filament is performed, as follows: Figure 5 As shown, Figure 5 Figure a shows the microscopic morphology characterization results of the membrane fiber cross section, which shows that the outer diameter of the membrane fiber is 297 μm and the wall thickness is 37 μm. Figure b shows the morphology characterization results of the external separation layer of the membrane fiber, which shows that there is a distinct and dense separation layer on the surface of the membrane fiber, giving the membrane fiber good selectivity.

[0033] Example 2 A method for preparing a high-permeability polyimide helium gas separation membrane includes the following steps: S1. Preparation of casting solution: Under an argon atmosphere, equimolar amounts of 6FDA and APBIA were dissolved in NMP, and the mixture was subjected to a condensation reaction at a gradient temperature of 180-190℃ for 18 h to obtain a 6FDA-APBIA resin with a weight-average molecular weight of 400,000.

[0034] 6FDA-APBIA resin with a weight-average molecular weight of 400,000 was vacuum dried at 120°C for 2 hours, and then dissolved in a mixed solvent of NMP and anhydrous ethanol at a mass ratio of 70:30. The mixture was stirred at 200 rpm to precisely control the solid content of 6FDA-APBIA resin in the casting solution to 15 wt%. The mixture was continuously mechanically stirred at 60°C for 24 hours until completely dissolved, and then filtered under pressure at 50°C and vacuum degassed for 12 hours at a vacuum degree of -95 kPa to obtain a homogeneous and transparent casting solution.

[0035] S2. Dry-Wet Hollow Fiber Spinning: Start the spinning device and preheat the feed tank, delivery pipeline, and composite spinneret to a constant 25°C. The casting solution is delivered to the outer annulus of the spinneret via a precision gear pump, with the flow rate controlled at 4.5 mL / min. Simultaneously, the core solution is injected into the central tube; the core solution is a mixture of N-methylpyrrolidone and water at a mass ratio of 80:20, with a flow rate of 4.5 mL / min. The nascent filaments extruded from the spinneret pass through a 100 mm air gap and then solidify in a 25°C deionized water coagulation bath. The filaments are then axially stretched and wound using a take-up roller at a take-up speed of 25 m / min, yielding a nascent filament bundle.

[0036] S3. The steps are the same as in Example 1, to obtain the final high-permeability polyimide helium separation membrane.

[0037] Example 3 A method for preparing a high-permeability polyimide helium gas separation membrane includes the following steps: S1. Preparation of casting solution: Under an argon atmosphere, equimolar amounts of 6FDA and APBIA were dissolved in NMP, and the temperature was gradually increased to 180-190℃ for 3 h to undergo polycondensation reaction, resulting in a 6FDA-APBIA resin with a weight-average molecular weight of 150,000. 6FDA-APBIA resin with a weight-average molecular weight of 150,000 was vacuum dried at 120°C for 2 hours to remove adsorbed water. The dried 6FDA-APBIA resin was then dissolved in a mixed solvent of NMP and anhydrous ethanol at a mass ratio of 73:27, with stirring at 300 rpm to precisely control the solid content of 6FDA-APBIA resin in the casting solution to 24 wt%. The solution was continuously mechanically stirred at 60°C for 24 hours until completely dissolved, followed by pressure filtration at 50°C and vacuum degassing for 12 hours at -95 kPa to obtain a homogeneous and transparent casting solution.

[0038] S2. Dry-Wet Hollow Fiber Spinning: Start the spinning device and preheat the feed tank, delivery pipeline, and composite spinneret to a constant 25°C. The casting solution is delivered to the outer annulus of the spinneret via a precision gear pump, with the flow rate controlled at 4.5 mL / min. Simultaneously, the core solution, a mixture of N-methylpyrrolidone and water at a mass ratio of 80:20, is injected into the central tube at a flow rate of 4.5 mL / min. The nascent membrane fibers extruded from the spinneret pass through a 100 mm air gap and then solidify in a 25°C deionized water coagulation bath. The membrane fibers are axially stretched and wound using a take-up roller at a take-up speed of 25 m / min to obtain a nascent membrane fiber bundle.

[0039] S3. The steps are the same as in Example 1, and the final high-permeability polyimide helium separation membrane is obtained.

[0040] Example 4 A method for preparing a high-permeability polyimide helium gas separation membrane includes the following steps: S1. Preparation of casting solution: Under an argon atmosphere, equimolar amounts of 6FDA and APBOA are dissolved in NMP and the temperature is gradually increased to 180-190 °C for polycondensation reaction for 4 h to obtain 6FDA-APBOA resin with a weight average molecular weight of 200,000. 6FDA-APBOA resin with a weight-average molecular weight of 200,000 was vacuum dried at 120°C for 2 hours to remove adsorbed water. The dried 6FDA-APBOA resin was dissolved in a mixed solvent of NMP and anhydrous ethanol at a mass ratio of 70:30, and the solid content of 6FDA-APBOA resin in the casting solution was precisely controlled to be 20 wt%. The solution was continuously mechanically stirred at 60°C for 24 hours until completely dissolved, and then filtered under pressure at 50°C and degassed under vacuum for 12 hours to obtain a homogeneous and transparent casting solution.

[0041] The structural formula of 6FDA-APBOA resin is: .

[0042] S2. Dry-Wet Hollow Fiber Spinning: Start the spinning device and preheat the feed tank, delivery pipeline, and composite spinneret to a constant 25°C. The casting solution is delivered to the outer annulus of the spinneret via a precision gear pump, controlling the flow rate at 4.5 mL / min. Simultaneously, the core solution, a mixture of N-methylpyrrolidone and water at a mass ratio of 80:20, is injected into the central tube at a flow rate of 4.5 mL / min. The nascent membrane fibers extruded from the spinneret pass through a 100 mm air gap and then solidify in a 25°C deionized water coagulation bath. The membrane fibers are axially stretched and wound using a take-up roller at a take-up speed of 25 m / min to obtain a nascent membrane fiber bundle.

[0043] S3. The steps are the same as in Example 1, and a high-permeability polyimide helium gas separation membrane is obtained.

[0044] Comparative Example 1 The only difference from Example 1 is that the take-up speed in step S2 is 10 m / min.

[0045] Comparative Example 2 The only difference from Example 1 is the spinning temperature. In step S2, the feed tank, conveying pipeline and composite spinneret are all preheated to 60°C for spinning.

[0046] Comparative Example 3 The only difference from Example 1 is that step S1 uses 6FDA-APBIA resin with a weight-average molecular weight of 50,000. The preparation method of 6FDA-APBIA resin with a weight-average molecular weight of 50,000 is as follows: under an argon atmosphere, equimolar amounts of 6FDA and APBIA are dissolved in NMP, and then the temperature is gradually increased to 180-190 °C for a polycondensation reaction for 1 h.

[0047] Comparative Example 4 The only difference from Example 1 is that in step S1, the solid content of 6FDA-APBIA resin in the casting solution is controlled to be 35wt%.

[0048] Comparative Example 5 This comparative example is used to investigate the effect of introducing a high proportion of poor solvent into the casting solution on the membrane performance. The only difference from Example 1 is that in step S1, the dried 6FDA-APBIA resin is dissolved in a mixed solvent prepared by mixing good solvent NMP and poor solvent anhydrous ethanol at a mass ratio of 55:45.

[0049] Comparative Example 6 The only difference from Example 1 is that the solidification bath temperature in step S2 is increased to 60°C.

[0050] Comparative Example 7 The only difference from Example 1 is that the take-up speed in step S2 is 40 m / min.

[0051] Performance Testing and Analysis The separation membranes prepared in Examples 1-4 and Comparative Examples 1-7 were assembled into a single membrane testing device. Under test conditions of 25°C and an inlet pressure of 0.2 MPa, the permeation rates of the membranes for pure He and pure CH4 were measured, and the selectivity was calculated. The selectivity calculation formula is as follows: In the formula, This represents the ideal selectivity of the separation membrane for helium and methane; and These represent the permeation flux of pure helium and pure methane under the same test temperature and pressure (commonly measured in GPUs).

[0052] Burst pressure test: One end of the monofilament of the separation membrane is completely sealed with adhesive such as epoxy resin, and the other end is fixed and connected to high-pressure nitrogen. At the same time, the maximum pressure value (burst pressure) when the membrane filament ruptures is measured by gradually increasing the inlet gas pressure.

[0053] The mechanical strength test method is as follows: a microcomputer-controlled universal testing machine is used for measurement. A membrane filament of a certain length is fixed at both ends in the upper and lower clamps of the instrument. An initial test gauge length is set, and the membrane filament is stretched uniformly at a constant stretching rate until it breaks under room temperature conditions. The mechanical strength of the separation membrane is recorded and calculated by the instrument's built-in software.

[0054] Each group of samples was tested in parallel 10 times and the average value was taken. The results are shown in Table 1: Table 1 Test results of the examples and comparative examples

[0055] As can be seen from the data in Table 1, compared with Example 1: Comparative Example 1 showed that the take-up speed was reduced from 25 m / min to 10 m / min, demonstrating that a moderate take-up speed makes it easier to obtain a high-permeability helium separation membrane.

[0056] Comparative Example 2 showed that increasing the spinning temperature from 25℃ to 60℃ improved the selectivity of hollow fiber membrane materials.

[0057] Comparative Example 3 reduced the weight-average molecular weight of the fluorinated polyimide resin from 250,000 to 50,000. The results showed that the selectivity of Comparative Example 3 was only 4.5, indicating that the control of the weight-average molecular weight of the present invention between 100,000 and 400,000 can ensure the formation of a sufficiently effective physical entanglement network between the polymer chains, thereby constructing a dense and defect-free selective separation skin during the phase transformation process to maintain excellent gas sieving ability and selectivity.

[0058] Comparative Example 4 increased the solid content of the casting solution from 18% to 35%, but the helium permeation flux was only 18.7 GPU. This shows that excessively high casting solution concentration leads to a significant increase in the thickness of the dense skin layer formed after phase transformation, which greatly increases the mass transfer resistance of the gas and significantly reduces the flux.

[0059] Comparative Example 5 introduced 45% anhydrous ethanol, a poor solvent, into the casting solution. This significantly reduced both permeation flux and selectivity, with the permeation flux falling below 250 GPU and the selectivity dropping below 60. This demonstrates that the appropriate proportion of poor solvent has a significant impact on the helium permeation flux and He / CH4 selectivity of the separation membrane.

[0060] In Comparative Example 6, increasing the coagulation bath temperature significantly reduced the helium / methane selectivity of the membrane, indicating that excessively high coagulation bath temperatures drastically accelerate the bidirectional diffusion rate between solvents and non-solvents, leading to overly intense transient phase separation. This easily generates micropores or structural defects on the separation skin surface, completely destroying the membrane's precise molecular sieving mechanism for gases.

[0061] In Comparative Example 7, the take-up speed in step S2 was 40 m / min. The helium / methane selectivity of the membrane decreased significantly. Excessive take-up speed can cause excessive mechanical tensile stress on the polymer macromolecular chains on the membrane surface, leading to stress concentration and even inducing microcrack defects, thus destroying the integrity of the dense surface layer. Therefore, the take-up speed must be controlled within a reasonable range.

[0062] In summary, the indispensability of the technical features of this invention has been verified by considering the winding speed, spinning temperature, resin molecular weight, fluorine-containing structure, solid content, and solvent system.

[0063] The separation membranes of Examples 1-4 of this invention were compared with those in the published literature (WANG Y, et al. Fabrication of defect-free benzimidazole polyimide hollow fiber membranes for high-performance gas separation. Journal of Membrane Science, 2026, 745: 125246.), and the results are as follows: Figure 6As shown, the separation membranes prepared in Examples 1-4 of this invention exhibit significantly better overall performance in terms of He / CH4 selectivity and permeation flux than the polyimide hollow fiber membranes (PEI, ZIF93@P84, P84, Matrimid 5218, PSF, PSF / MWCNTs) reported in the literature. This fully demonstrates that this invention successfully constructs a dense and uniform physically entangled network separation layer by optimizing the molecular weight of polyimide and the spinning process. This structure not only provides a fast transport channel for helium molecules with extremely low resistance but also maintains extremely high gas molecule sieving accuracy, effectively overcoming the trade-off effect between permeability and selectivity commonly faced by traditional polymer gas separation membranes.

[0064] The stress-strain analysis of the separation membranes in Examples 1-4 was performed, and the results are as follows: Figure 7 As shown, the separation membranes prepared in Examples 1-4 of this invention all exhibit excellent and controllable mechanical properties. Specifically, the tensile strength (i.e., fracture stress) of each example ranges from approximately 53 MPa to 72 MPa, and the elongation at break ranges from approximately 12% to 21.5%. Among them, Example 4 exhibits the highest tensile strength (>70 MPa), possessing extremely strong resistance to high-pressure deformation; while Example 2 exhibits the best flexibility (elongation at break >21%). This tensile curve, composed of typical yield and plastic deformation, fully demonstrates that the casting solution system of this invention promotes the formation of a highly dense and entangled physical network structure of polymer chains during solidification, completely overcoming the fatal defect of traditional high free volume polyimide membranes being prone to brittle fracture, and fully meeting the actual packaging and long-term operation requirements of industrial high-pressure gas separation components.

[0065] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the inventive concept, and these all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high-permeability polyimide helium gas separation membrane, characterized in that, Includes the following steps: S1. Dissolve the fluorinated polyimide resin in a mixed solvent, stir until homogeneous, and after degassing, obtain a casting solution with a solid content of 15-30 wt%. The fluorinated polyimide resin is prepared by polycondensation reaction of a dianhydride monomer and a diamine monomer. The diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole or 2-(4-aminophenyl)-5-aminobenzoxazole, and the dianhydride monomer is 4,4'-(hexafluoroisopropene)phthalic anhydride. The weight-average molecular weight of the fluorinated polyimide resin is 100,000-400,000. S2. The casting solution and core solution obtained in step S1 are subjected to dry-wet hollow fiber spinning through a spinneret. The nascent film filaments extruded from the spinneret pass through an air gap and a coagulation bath in sequence. Then, the film filaments are axially stretched and wound using a take-up roller to obtain a nascent film filament bundle. The spinning temperature is 25°C, the length of the air gap is 0.1-200 mm, the flow rate of the casting solution and the core solution is 0.6-6.0 mL / min, the coagulation bath is a deionized water coagulation bath at 0-40°C, and the take-up speed of the take-up roller is 15-35 m / min. S3. The nascent membrane fiber bundles obtained in step S2 are sequentially immersed in deionized water, anhydrous ethanol and n-hexane for solvent exchange, and then dried to obtain the high-permeability polyimide helium separation membrane.

2. The preparation method according to claim 1, characterized in that, The mixed solvent comprises a good solvent and a bad solvent in a mass ratio of 60:40 to 90:

10. The good solvent includes one or more of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide. The bad solvent includes one or more of methanol, ethanol, propanol, isopropanol, and tetrahydrofuran.

3. The preparation method according to claim 1, characterized in that, The dissolution process in step S1 specifically involves: continuously stirring at 60-80°C for 12-24 hours until the fluorinated polyimide resin is completely dissolved; the degassing treatment is vacuum degassing or atmospheric pressure degassing.

4. The preparation method according to claim 1, characterized in that, In step S2, the core fluid is a mixed solution of N-methylpyrrolidone and water with a mass ratio of 90:10 to 80:

20.

5. The preparation method according to claim 1, characterized in that, In step S3, the solvent exchange process is as follows: soaking in deionized water for 1-48 hours at a water temperature between 10-40 °C, soaking in ethanol for 0.1-48 hours, and soaking in n-hexane for 0.1-48 hours.

6. A high-permeability polyimide helium separation membrane prepared by the preparation method according to any one of claims 1-5, characterized in that, The separation membrane is an asymmetric hollow fiber membrane with a dense skin layer and a porous support layer; under test conditions of 25°C and 0.2 MPa, its helium permeation flux is 600-1000 GPU, its helium / methane selectivity is 80-120, and its burst pressure is above 5.0 MPa.

7. The application of the high-permeability polyimide helium separation membrane as described in claim 6 in the fields of natural gas helium extraction, helium recovery, or helium purification.

Citation Information

Patent Citations

  • Crosslinking polyimide gas separation membrane and preparation method

    CN105289337A

  • Aromatic co-polyimide gas separation membranes derived from 6FDA-6fpda-type homo-polyimides

    CN113631248A

  • Copolyimide film, preparation method and application of copolyimide film in helium purification

    CN113996193A

  • Auto-polymerization microporous polymer fluorinated membrane as well as preparation method and application thereof

    CN113337095A

  • Polyamide-imide hollow fiber membrane and helium separation membrane

    CN115888426A